2000
DOI: 10.1177/0272989x0002000114
|View full text |Cite
|
Sign up to set email alerts
|

Interpretive Review : Feasibility and Effects of Decision Aids

Abstract: Decision aids for patients have recently been introduced in health care. A literature review was conducted to address the following research questions: 1) which types of decision aids have been developed?; 2) to what extent are they feasible, and acceptable to patients and health care providers?; 3) do decision aids affect the decision-making process and patients' outcomes? Thirty non-controlled (e.g., one-group-only designs) and controlled studies (e.g., randomized experimental designs) were identified. Decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
118
1
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(125 citation statements)
references
References 54 publications
4
118
1
2
Order By: Relevance
“…Decision aids have been found to be feasible and acceptable to patients and to increase the agreement between patients' values and decisions (Molenaar et al, 2000). A recent systematic review found that DAs improve patients' knowledge and realistic expectations of treatment options, reduce decisional conflict, and stimulate patients to play a more active role in decision-making (O'Connor et al, 2002).…”
mentioning
confidence: 99%
“…Decision aids have been found to be feasible and acceptable to patients and to increase the agreement between patients' values and decisions (Molenaar et al, 2000). A recent systematic review found that DAs improve patients' knowledge and realistic expectations of treatment options, reduce decisional conflict, and stimulate patients to play a more active role in decision-making (O'Connor et al, 2002).…”
mentioning
confidence: 99%
“…Information only includes interventions aimed primarily at the exchange of information, by means of persuasive communication or information brochures [22]. Patients need information to [7]:…”
Section: Patient Education: Definition Educational Interventions Andmentioning
confidence: 99%
“…Such an exchange of information is an essential element of a process of shared decision making between patients and their doctors [22]. It is necessary to educate patients on the nature of the outcomes and the benefits and risks of the procedures to involve them in the decision-making process and enable them to achieve fully informed consent [10].…”
Section: Patient Education: Definition Educational Interventions Andmentioning
confidence: 99%
See 2 more Smart Citations